تأثير استخدام المادة متغيرة الطور (PCM) على إنتاجية المقطر الصندوقي الشمسي - جورج, رامي; أحمد, مها; بدور, أنس (Latakia University Journal -Engineering Sciences Series, 2016)
The objective of this investigation is to study the influence of application of phase change material (PCM) in solar basin stills for improving its productivity. The experimental results of this investigation showed that using phase change material (paraffin wax) in solar basin still improved its daily productivity, which increased with increasing the mass of phase change material. The highest increase ratio of daily productivity was 26.3[%] when using 3.5[kg] of phase change material in plastic case, and it was 34.74[%] when using 4.5[kg] of phase change material (PCM) in metal case. Also the experimental results of this investigation showed an increase in the period of working basin still provided with phase change material compared with basin still without phase change material. This is owing to the latent heat stored in phase change material, which is emitted to water when solar radiation decreases. This results in longer period of work for the basin still. يهدف هذا البحث إلى إجراء دراسة تجريبية لتأثير استخدام المادة متغيرة الطور (PCM) في المقطرات الصندوقية الشمسية من أجل تحسين إنتاجيتها.أظهرت نتائج البحث التجريبية المنجزة أن استخدام المادة متغيرة الطور (الشمع البارافيني) في المقطر الصندوقي الشمسي أدى إلى تحسين في إنتاجيته اليومية، حيث تبين أنها تزداد مع زيادة كمية المادة متغيرة الطور المستخدمة، حيث بلغت أعلى قيمة لنسبة الزيادة في الإنتاجية اليومية 26.3[%] عند استخدام 3.5[kg] من المادة متغيرة الطور الموضوعة ضمن عبوات بلاستيكية، والقيمة 34.74[%] عند استخدام 4.5[kg] من المادة متغيرة الطور (PCM) الموضوعة ضمن عبوات معدنية. كما أظهرت نتائج البحث التجريبية ازدياد فترة عمل المقطر الصندوقي الشمسي المزود بالمادة متغيرة الطور مقارنة بالمقطر من دون مادة متغيرة الطور. وهذا ناتج عن الطاقة الحرارية الكامنة المخزنة في المادة متغيرة الطور والتي تقدمها للماء عند انخفاض شدة الإشعاع الشمسي مما يؤدي إلى تبخر الماء واستمرار المقطر بالعمل لفترة زمنية أطول.